2006
DOI: 10.1200/jco.2005.04.9866
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Interstitial Lung Disease, Antitumor Response, and Survival in Non–Small-Cell Lung Cancer Patients Treated With Gefitinib

Abstract: ILD is a serious adverse effect of gefitinib in the clinical setting that cannot be ignored. However, patient selection based on sex and smoking history can minimize ILD risk and maximize the clinical benefit of gefitinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
220
5
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(236 citation statements)
references
References 26 publications
9
220
5
2
Order By: Relevance
“…The relatively high incidence of ILD (3.5-5.8%) in patients treated with gefitinib has been reported in Japan. It also revealed that male gender, ever-smokers, poor PS and the coincidence of interstitial pneumonia were predictive factors for the development of ILD (Yoshida, 2005;Ando et al, 2006). Although these predictive factors contrast with those for the presence of an EGFR mutation, two of the 28 patients with an EGFR mutation developed ILD in our study.…”
Section: Predictors Of Survival Benefits With Gefitinib M Satouchi Et Almentioning
confidence: 46%
See 1 more Smart Citation
“…The relatively high incidence of ILD (3.5-5.8%) in patients treated with gefitinib has been reported in Japan. It also revealed that male gender, ever-smokers, poor PS and the coincidence of interstitial pneumonia were predictive factors for the development of ILD (Yoshida, 2005;Ando et al, 2006). Although these predictive factors contrast with those for the presence of an EGFR mutation, two of the 28 patients with an EGFR mutation developed ILD in our study.…”
Section: Predictors Of Survival Benefits With Gefitinib M Satouchi Et Almentioning
confidence: 46%
“…Several subsequent retrospective studies have reported that female gender, adenocarcinoma histology, bronchioloalveolar subtype, never-smokers and patients with favourable PS are predictive factors of response Kim et al, 2005;Lim et al, 2005;Ando et al, 2006). EGFR mutation has been reported as a predictor of efficacy of gefitinib and erlotinib (Lynch et al, 2004;Pao et al, 2004).…”
Section: Predictors Of Survival Benefits With Gefitinib M Satouchi Et Almentioning
confidence: 99%
“…A retrospective study of 1976 consecutive patients treated with gefitinib at 84 institutions showed that the incidence of ILD was 3.5% and the mortality rate was 1.6%. Several risk factors for the development of gefitinibinduced ILD were identified in the Japanese population: a history of pulmonary fibrosis, a history of smoking, a poor performance status, and a male sex (Ando et al, 2006). A similar incidence of ILD (4.6%) was also noted in association with erlotinib chemotherapy in Japanese phase II trials .…”
Section: Interstitial Lung Disease Associated With Gefitinib and Erlomentioning
confidence: 63%
“…Interstitial lung disease is the most problematic toxicity in gefitinib treatment in Japan where an incidence of 3.5% and a fatality rate of 1.6% have been reported (Inoue et al, 2003;Ando et al, 2006). Accordingly, in the present trial, we planned to conduct biweekly chest CT for early detection of ILD during the initial treatment period.…”
Section: Discussionmentioning
confidence: 99%